MON-001 Assessment of Endocrine Clinic Attendance Rates to Guide Interventions to Reduce Patient No-Show Rates - Cha, Jeeyeon (J Endocr Soc, 2019)
As a part of our endocrine fellowship quality improvement training, we sought to improve patient access to endocrine outpatient clinic appointments at our institution. From the physician perspective, patients who do not show up for a 30-45 minute new patient visit slot disrupt clinic flow and limits access for other patients. Therefore, we decided to focus our attention on reducing the new patient no-show rate. Here, we assessed the efficacy of our current scheduling system from 2014-2016. This analysis was performed as part of a quality improvement project to inform future interventions. Previously, only a few studies have attempted to identify baseline no-show rates (1,2). Our institution utilizes an automated telephone appointment reminder system (Televox) which calls patients three to four business days prior to a scheduled appointment and gives the patient an opportunity to confirm or cancel the appointment. Televox data for 7,556 patients over 34 months (1/2014-10/2016) revealed a 95% show frequency for patients who confirmed their appointment, 82% show frequency for patients for which there was no response to the Televox reminder, and 78% show frequency of patients who were not reached (Televox call not made). P-Chart of the show frequencies of patients who did not respond or were not reached fluctuated between 70-90% over this period. This analysis shows that new patients who did not respond or were not reached are a potential target for intervention. By identifying this cohort early, we will be able to implement intervention and reschedule patients in a timely manner to improve clinic flow and clinic access. References: 1. Mohamed, K., Mustafa, A., Tahtamouni, S., Taha, E., Hassan, R. A Quality Improvement Project to Reduce the ‘No Show’ Rate in a Paediatric Neurology Clinic. BMJ Quality Improvement Reports. pii: u209266.w3789, 2016. PMID: 27651897 2. Santiago, V.A., Warwick, K., Ratnakumarasuriyar, S., Oyewumi, A., Robinson, S., Sockalingam, S. Evaluation of a Patient-Care Planning Intervention to Improve Appointment Attendance by Adults After Bariatric Surgery. Canadian Journal of Diabetes, pii: S1499-2671(17)31001-8, 2018. PMID: 30121163 Sources of Research Support: None